Дышетись: пьесаос / И. М. Данилов - Данилов Иван Михайлович (Удмуртия, 1985)
Экземпляры: Селтинская районная библиотека (аб) (20190111) / Инвентарный номер: 105342 / Цена: 0.25 / Авт.знак: Д18 / ГРНТИ: 17.82 / ББК: 84(2Рос=Удм)6